Pengembangan digital resistivity meter multielektroda otomatis untuk konfigurasi Schlumberger (Development of an automatic multi-electrode digital resistivity meter for the Schlumberger configuration) - Erin Ficrah Huda; - Yohandri (PILLAR OF PHYSICS, 2020)
Prototype digital multi-electrode automatic resistivity meter is a prototype that is used to measure ground resistivity with 16 electrodes based on the ohm law principle. By selecting four electrodes as a measuring point, then injecting voltage through the two current electrodes, the potential difference between the two electrodes can be detected. Current and voltage data obtained can determine the value of resistivity or soil resistivity. This research is a type of research and development that functions to develop existing products. From the results of the study, it can be stated four results consisting of internal testing results, product manufacturing results and initial field testing results or limited trials. The results of internal testing are looking at the characteristics of the current detection circuit, then testing the relay module and multiplexer module. The products are made up of prototype boxes, cable electrodes, 16 nail electrodes and, 12-volt batteries. Preliminary field test results on a laboratory scale for current and voltage measurements with error percentages from 0,8% to 31,8% and 0,098% to 11,76%, respectively. Limited field test results for resistivity measurements at three different locations obtained an average accuracy of 78,05%; 78,89% and 84,05%, respectively. While the average accuracy was 77,50%, 99,74% and 99,41%, respectively.